Biochemical and functional characterization of histone H1-like proteins in procyclic Trypanosoma brucei brucei - Burri, Markus; Schlimme, Wolfram; Betschart, Bruno; Kämpfer, Urs; Schaller, Johann; Hecker, Hermann (My University, 1993)
Four variants and/or posttranslational modifications of histone H1-like proteins of Trypanosoma brucei brucei procyclic culture forms were extracted with 0.25N HCl from isolated nuclei and analyzed by two-dimensional gel electrophoresis. The amino acid composition of these proteins, their ability to space nucleosomes regularly and to induce salt-dependent condensation of the chromatin indicated their histone H1 nature. On the other hand, the histone H1-like proteins clearly differed from their higher-eukaryote counterparts by their weak interaction with DNA under low-salt conditions. As a consequence, intact nucleosome filaments were prepared according to a new preparation protocol especially adapted to the unstable chromatin of T. b. brucei. Our results indicate that the biochemical properties of the histone H1-like proteins contribute to the structural and functional differences between the chromatin of procyclic T. b. brucei and that of higher eukaryotes.